2015
DOI: 10.1002/lsm.22462
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of circular wound healing in rats after exposure to 808‐nm laser pulses during specific healing phases

Abstract: Histological and morphometric results showed that high-power, low-energy application has the best effect when first applied 24 hours post-wounding (late inflammatory, early proliferative stage) as demonstrated by increases in granulation tissue, fibroblasts and collagen deposition, which lead to faster rates of wound contraction and thus accelerated healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Consistent with this, histological observations also demonstrated enhanced wound repair as reflected by the reduced infiltration of inflammatory cells, increased neo-vascularization, fibrogenesis, collagen accumulation and faster re-epithelialization in 810 nm laser with PW 10 Hz irradiated group. These findings were in agreement with previous studies which have shown that NIR laser (808–830 nm) irradiation significantly increases granulation tissue formation, fibroblasts and collagen deposition on dermal wounds, which lead to accelerated healing processes [19,20,36]. …”
Section: Discussionsupporting
confidence: 93%
“…Consistent with this, histological observations also demonstrated enhanced wound repair as reflected by the reduced infiltration of inflammatory cells, increased neo-vascularization, fibrogenesis, collagen accumulation and faster re-epithelialization in 810 nm laser with PW 10 Hz irradiated group. These findings were in agreement with previous studies which have shown that NIR laser (808–830 nm) irradiation significantly increases granulation tissue formation, fibroblasts and collagen deposition on dermal wounds, which lead to accelerated healing processes [19,20,36]. …”
Section: Discussionsupporting
confidence: 93%
“…This confliction might possibly be attributed to different laser parameters, the difference between the employed methods (such as the site of the wound, animal or human study, scales to measure, healing stage) and laser parameters. For example, in the study of Tabakoglu et al, 28 the wound size was half the size of the ulcer examined in the present study; therefore, it is predicted that wound closure in that study was more due to the contraction mechanism rather than healing by secondary intention; and as the wounds in laser group have higher amounts of collagen, the susceptibility to contract is higher in this group than control group. 32 Collagen fibers in laser group showed considerably higher levels than GF group.…”
Section: Discussionmentioning
confidence: 44%
“…There are a large number of studies which demonstrated healing promotion effects for laser. [28][29][30] The mechanism of low-level laser therapy in healing promotion is not completely understood yet; however, it is supposed that laser efficacy is not only due to its heating effects but rather to its photochemical, photophysical and/ or photobiological effects; many name these as photobiomodulation. It seems that laser illumination can improve local circulation, cell proliferation, and collagen synthesis by increasing cell access to ATP.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated in vivo clinical effects of low-level laser therapy (LLLT) on second-degree thermal burns in rats. LLLT is an important intervention for wound healing that has been shown to create beneficial effects on the stimulation of the extracellular matrix, myofibroblasts, and granulation tissue activities for the skin healing process [23][24][25]. The presence of myofibroblasts creates a centripetal contraction from the edges of the burn lesion.…”
Section: Discussionmentioning
confidence: 99%